Tracing Manuscripts in Time and Space through Paratexts - Ciotti, Giovanni (Studies in Manuscript Cultures, 2016)
As records of the link between a manuscript and the texts it contains, paratexts document many aspects of a manuscript's life: production, transmission, usage, and reception. Comprehensive studies of paratexts are still rare in the field of manuscript studies, and the universal categories of time and space are used to create a common frame for research and comparisons. Contributions in this volume span over three continents and one millennium.